Diversité des formes de croissance de Juniperus communis L. dans les stations refuges des hautes montagnes du bassin versant de la Moulouya (Maroc) - Mustapha Rhanem (Physio-Géo)
In Morocco, Juniperus communis L. (common juniper), which tends to be too automatically qualified as a phanerophyte because its belongs to the woody arborescent species group, acquires a dwarfed shape, always thick, and often takes on a typical mound appearance even if a wide range of growth forms exist for both isolated tufts and those grouped in mass more or less compacts. In addition to nivo-aeolian processes, topography and edaphic conditions specific to each station play a key role in the expression of this polymorphism.Whatever the morphologies adopted in response to their microenvironment, juniper tufts grows most often as creeping coppice, small rugs or wide carpets. Their spreading on steep slopes with a dispersed and sporadic distribution contributes to a very characteristic tiger mosaic pattern within the general physiognomy of the oromediterranean vegetation cover. For that and for its relict species status, the common juniper deserves here to be protected.